2016
DOI: 10.1182/bloodadvances.2016000208
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deep sequencing in primary myelofibrosis

Abstract: Key Points• More than 80% of patients with PMF harbor DNA variants/mutations other than JAK2/ CALR/MPL.• Some of these variants/mutations adversely affect overall or leukemia-free survival independent of conventional risk stratification.A myeloid neoplasm-relevant 27-gene panel was used for next-generation sequencing of bone marrow or whole blood DNA in 182 patients with primary myelofibrosis (PMF). DNA sequence variants/mutations other than JAK2/CALR/MPL were detected in 147 patients (81%), with the most freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
210
3
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 194 publications
(237 citation statements)
references
References 22 publications
15
210
3
9
Order By: Relevance
“…A recent study of 182 MF patients identified many with JAK2 V617F and SRSF2 P95 co-mutation, including several aged ,70 years (n 5 21, age range 39-84 years). 19 Taken together, these observations suggest that younger individuals with SRSF2-mutant clonal hematopoiesis may be at a high risk of progression to a hematological neoplasm.…”
mentioning
confidence: 80%
“…A recent study of 182 MF patients identified many with JAK2 V617F and SRSF2 P95 co-mutation, including several aged ,70 years (n 5 21, age range 39-84 years). 19 Taken together, these observations suggest that younger individuals with SRSF2-mutant clonal hematopoiesis may be at a high risk of progression to a hematological neoplasm.…”
mentioning
confidence: 80%
“…1 However, a subset (10-15%) of MPN Ph-patients, the so-called triplenegative (TN), do not present any of those driver mutations, but may harbor others that might be associated with inferior overall survival (OS) or leukemic transformation. 2,3 Based on this, and considering that there are just a few studies on this subgroup of patients, our aim was to assess the utility in terms of diagnosis and prognosis by performing targeted deep sequencing (TDS) of myeloid-related genes in TN MPN patients.…”
Section: Diagnostic and Prognostic Contribution Of Targeted Ngs In Pamentioning
confidence: 99%
“…In transplant‐eligible patients, the change in outlook might encourage pursuing AlloSCT sooner than later or provide additional comfort for decision to defer. We are well aware of the existence of other adverse mutations in PMF (Tefferi et al , ), but focused on ASXL1 and SRSF2 because of their relatively higher prevalence (36% for ASXL1 and 18% for SRSF2 ), compared to other adverse mutations (1% for EZH2 and 3% for IDH2 ), and also because of the abundance of supporting data for the former (Vannucchi et al , ).…”
mentioning
confidence: 99%